Evaluation of the USDA Fresh Fruit and Vegetable Program in Wisconsin Schools : Parent and Teacher Surveys. - Lauersdorf, Brandon; Lutz, Beth; Glodowski, Kathryn R. (My University, 2009)
In November 2005, Wisconsin was selected to participate as an expansion state in the existing U.S. Department of Agriculture (USDA)Fresh Fruit and Vegetable Program, which was created for the purpose of improving nutrition and reducing the prevalence of childhood overweight and obesity. In conjunction with the last round of student surveys (March, 2007), we used survey instruments to collect data from parents and teachers of elementary school students participating in the program. This study focuses on quantitative and qualitative responses from teachers and parents as indicators of program effectiveness.
Color poster with text and graphs describing research conducted by Brandon Lauersdorf, Beth Lutz, and Kathryn Glodowski, advised by Eric Jamelske and Lari Bica.
Keywords: Fresh Fruit and Vegetable Program (Wis.); Nutrition--Study and teaching (Elementary)--Wisconsin; School children--Nutrition--Wisconsin; School children--Food--Wisconsin; Posters